Analysis of The Use of Urine Catheters on Catheter-Related Urinary Tract Infections with The Infection Control Risk Assessment Method on Aspects of Knowledge and Attitudes in Hospitals in Yogyakarta - Kusbaryanto, Kusbaryanto; Nishihara, Alika Anisa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Healthcare-Associated Infections (HAIs) have now become the cause of an increase in morbidity, mortality and length of hospital stay. Catheter-associated Urinary Tract Infections (CAUTI) account for nearly 40% of all nosocomial infections. This reflects the poor quality of health services. This study aims to analyze the use of urinary catheters for CAUTI with the Infection Control Risk Assessment (ICRA) method in Indonesian hospitals. The design of this research is descriptive quantitative and qualitative. The population in the study were all nurses who worked in the hospital. The sample used in this study to determine the level of knowledge and attitudes related to urinary catheter placement were all nurses who worked in the Internal Medicine, Surgery, Geriatrics and Emergency Units of Panembahan Senopati Hospital Bantul, which collected 61 respondents. The sampling technique used is random sampling. Inclusion criteria are a 1-year nurse working period, and minimum education D3. The exclusion criteria were respondents who did not fill out the questionnaire completely. Informants in this study were IPCN, IPCLN, internal medicine specialists, emergency room nurse coordinators, and nurses in the inpatient ward. The rate of urinary catheter insertion was high (29.51%), moderate (63.93%), and low (6.6%). On a deeper knowledge of catheter insertion, which is well-informed. The attitude of urinary catheter placement was good (73.8%) and bad (26.2%). On a deeper attitude to catheter insertion, the scores are good. Nurses have a moderate level of knowledge and have a good attitude about urinary catheter placement. The most potential risks have been identified. Each potential has risks to take advantage of each and is related to each other. It is best to consider relevant strategies to address the problem.Abstrak: Healthcare Associated Infections (HAIs) kini telah menjadi penyebab peningkatan morbiditas, mortalitas dan lama rawat inap. Infeksi Saluran Kemih terkait kateter (CAUTI) menyumbang hampir 40% dari semua infeksi nosokomial. Hal ini mencerminkan buruknya kualitas pelayanan kesehatan. Penelitian ini bertujuan untuk menganalisis penggunaan kateter urin pada CAUTI dengan metode Infection Control Risk Assessment (ICRA) di rumah sakit Indonesia. Desain penelitian ini adalah deskriptif kuantitatif dan kualitatif. Populasi dalam penelitian ini adalah seluruh perawat yang bekerja di rumah sakit. Sampel yang digunakan dalam penelitian ini untuk mengetahui tingkat pengetahuan dan sikap terkait pemasangan kateter urin adalah seluruh perawat yang bekerja di Unit Penyakit Dalam, Bedah, Geriatri dan IGD RSUD Panembahan Senopati Bantul yang berjumlah 61 responden. Teknik pengambilan sampel yang digunakan adalah random sampling. Kriteria inklusi adalah: masa kerja perawat 1 tahun, pendidikan minimal D3. Kriteria eksklusi adalah responden yang tidak mengisi kuesioner dengan lengkap. Informan dalam penelitian ini adalah IPCN, IPCLN, spesialis penyakit dalam, koordinator perawat ruang gawat darurat, dan perawat di ruang rawat inap. Tingkat pemasangan kateter urin tinggi (29,51%), sedang (63,93%), rendah (6,6%). Pada pengetahuan yang lebih dalam tentang penyisipan kateter, yang diinformasikan dengan baik. Sikap pemasangan kateter urin baik (73,8%) dan buruk (26,2%). Pada sikap yang lebih dalam untuk penyisipan kateter, skornya bagus. Perawat memiliki tingkat pengetahuan sedang, memiliki sikap yang baik tentang pemasangan kateter urin. Risiko yang paling potensial telah diidentifikasi. Setiap potensi memiliki risiko yang dapat dimanfaatkan masing-masing dan saling berkaitan. Yang terbaik adalah mempertimbangkan strategi yang relevan untuk mengatasi masalah tersebut.